PCG-net: feature adaptive deep learning for automated head and neck organs-at-risk segmentation - Luan, Shunyao; Wei, Changchao; Ding, Yi; Xue, Xudong; Wei, Wei; Yu, Xiao; Wang, Xiao; Ma, Chi; Zhu, Benpeng (Frontiers in Oncology, 2023)
Radiation therapy is a common treatment option for Head and Neck Cancer (HNC), where the accurate segmentation of Head and Neck (HN) Organs-At-Risks (OARs) is critical for effective treatment planning. Manual labeling of HN OARs is time-consuming and subjective. Therefore, deep learning segmentation methods have been widely used.However, it is still a challenging task for HN OARs segmentation due to some small-sized OARs such as optic chiasm and optic nerve. To address this challenge, we propose a parallel network architecture called PCG-Net, which incorporates both convolutional neural networks (CNN) and a Gate-Axial-Transformer (GAT) to effectively capture local information and global context. Additionally, we employ a cascade graph module (CGM) to enhance feature fusion through message-passing functions and information aggregation strategies. We conducted extensive experiments to evaluate the effectiveness of PCG-Net and its robustness in three different downstream tasks. The results show that PCG-Net outperforms other methods, improves the accuracy of HN OARs segmentation, which can potentially improve treatment planning for HNC patients. In summary, the PCG-Net model effectively establishes the dependency between local information and global context and employs CGM to enhance feature fusion for accurate segment HN OARs. The results demonstrate the superiority of PCG-Net over other methods, making it a promising approach for HNC treatment planning.